Mempengaruhi Keputusan Pembelian: Strategi Pemasaran yang Efektif untuk Produk Hanasui di Era Digital (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to see how the influence of content marketing and direct marketing on the decision of Trunojoyo Madura University students from Lamongan to buy Hanasui products on the Shopee e-commerce platform. This study uses multiple linear regression analysis and involves 100 respondents who are students of Trunojoyo Madura University from Lamongan aged 18-22 years, active users of Shopee and have purchased Hanasui products at Shopee. The results showed that content marketing with interesting content that increases customer trust has a positive and significant effect on consumer purchasing decisions. Meanwhile, direct marketing, especially involving live streaming, increases customer engagement. These findings help Hanasui increase sales and customer loyalty and help marketers design more relevant campaigns in the competitive student market. This research is expected to serve as a reference for further research on digital marketing in a wider market segment.